Macbeth [videorecording (DVD)] - Buchanan, Judith; Mattinson, Thomas; Monkman, Kit; Wexler, Wom; Shakespeare, William, 1564-1616; Rowley, Mark, 1990-; Weaver, Al, 1981-; Mosaku, Wunmi (Trinity Creative Partnership, 2020)
The bold reimagining of Shakespeare's Macbeth delves into the shadowy corners of the human mind. Showcasing a visually striking style and a contemporary twist, this adaptation follows the gripping journey through madness, betrayal, and the haunting consequences of one's choices, all while maintaining the poignant language and themes of the original tragedy.